Transdifferentiation of canine mesenchymal stem cells into neuron-like cells by induction with Î²-mercaptoethanol - MILI, BHABESH; DAS, KINSUK; P, MADHUSOODAN A; KUMAR, KULDEEP; SAXENA, A C; BAG, SADHAN (The Indian Journal of Animal Sciences, 2021)
The objective of this study was to check whether β- mercaptoethanol in a culture medium can induce the neuronal differentiation of canine MSCs. The canine bonemarrow derived MSCs were first pre-inducted with 1 mM BME for 24 hrs followed by induction in a serum-free medium supplemented with 4 mM BME without FBS for another 6 days. Morphological changes in MSCs from spindle-shaped to neuron-like branching from the edges of the cells were noticed at the end of induction. These neuronlike cells were found positive for the immunophenotypic expression of different neural cell markers β-tubulin III, MAP-2 and Nestin. In RT-PCR analysis, it was also evident that the relative expressions of these representative genes were significantly higher in the differentiated cells. On the basis of our observations, it can be summarized that the BME induction of canine MSCs resulted in morphological changes that resembled neuron-like cells which were found to express the representative neuronal markers. Therefore, inducing canine MSCs with BME resulted in the generation of neuron-like cells that might be utilized for the prospective therapeutic applications in veterinary medicine.